Spinitectus aguapeiensis n. sp. (Nematoda: Cystidicolidae) from Pimelodella avanhandavae Eigenmann (Siluriformes: Heptapteridae) in the River Aguapeí, Upper Paraná River Basin, Brazil - Acosta, Aline Angelina [UNESP]; González-Solís, David; da Silva, Reinaldo José [UNESP] (Springer Nature, 2017)
Nematodes belonging to Spinitectus Fourment, 1883 (Nematoda: Cystidicolidae) were found in the intestine of Pimelodella avanhandavae Eigenmann (Siluriformes: Heptapteridae) from the Aguapeí River, Brazil. They represent a new species, Spinitectus aguapeiensis n. sp., which differs morphologically from its congeners in the body length, the number of spinose rings, the location of the excretory pore, the number of precloacal papillae and the length of the spicules. The new species is the first South American species within the genus with a remarkably spirally coiled posterior extremity in males and the largest spicules. It is also the second species with the highest number of precloacal papillae and has unique shape of the small spicule. Spinitectus aguapeiensis n. sp. is the first helminth species found in P. avanhandavae, the fourth species of this genus recorded in the River Paraná Basin and the sixth species of Spinitectus in South America.